Comprehension activities for reading in social studies and science - Nickelsen, LeAnn (New York : Scholastic, 2003)
Presents forty activities for increasing comprehension in social studies and science reading appropriate for students in fourth through eighth grade, featuring projects and activities for before, during, and after reading, and including graphic organizers and teaching tips.
"40 engaging before, during, and after-reading activities and reproducibles that help students get the most from textbooks and other nonfiction"--Cover.
"Grades 4-8"--Cover.
Includes bibliographical references.
Professional
Keywords: Creative activities and seat work; Reading comprehension; Reading; Science -- Study and teaching; Social sciences -- Study and teaching; Teaching -- Aids and devices; Creative activities; Reading comprehension; Reading; Science -- Study and teaching; Social sciences -- Study and teaching; Teaching -- Aids and devices